Age-Dependent Heterogeneity of Murine Olfactory Bulb Astrocytes - Klein, Marcel; Lohr, Christian; Droste, Damian (Frontiers in Aging Neuroscience, 2020)
Astrocytes have a high impact on the structure of the central nervous system, as they control neural activity, development and plasticity. Heterogeneity of astrocytes has been shown before, but so far only few studies have demonstrated heterogeneous morphology of astrocytes in relation to aging. In this study, we examined morphologic differences of astrocyte subpopulations in adult mice and the progression of these differences with age. We surveyed astrocytes in olfactory bulb slices of mice aged three months, one year and two years (three animals each age group), based on their appearance in anti-GFAP immunostaining. Based on this data we established three different types of astrocytes: type I (stellate), type II (elliptic) and type III (squid-like). We found that with advanced age of the mice, astrocytes grow in size and complexity. Major changes occurred between ages of three months and one year, while between one and two years no significant development in cell size and complexity could be detected. Our results show that astrocytes in the olfactory bulb are heterogeneous and undergo morphological transformation until late adolescence but not upon senescence. Structural plasticity is further substantiated by expression of vimentin in some astrocyte processes in all age groups.